The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1523/jneurosci.17-06-01959.1997
|View full text |Cite
|
Sign up to set email alerts
|

Trophic Support of Cultured Spiral Ganglion Neurons by Depolarization Exceeds and Is Additive with that by Neurotrophins or cAMP and Requires Elevation of [Ca2+]iwithin a Set Range

Abstract: Spiral ganglion neurons (SGNs) require both pre-and postsynaptic contacts to maintain viability. BDNF, chlorphenylthiocAMP, and depolarization (veratridine

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
234
1
4

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 191 publications
(254 citation statements)
references
References 64 publications
14
234
1
4
Order By: Relevance
“…The somewhat rough isolation procedure may contribute to the discrepancy in the yield of cells from embryonic or neonatal tissue (several thousands) compared with cells from adult inner ear (several hundreds). Previous studies (Zheng and Gao, 1996;Hegarty et al, 1997;Altschuler et al, 1999;Rubel and Fritzsch, 2002;Whitlon, 2004) have demonstrated that NT-3, BDNF, FGF-2, and GDNF can promote SGN survival during development or following deafness caused by ototoxic compounds and noise and trauma. We have extended these findings and demonstrated that coadministration of FGF-2 and GDNF can promote long-term survival of targetdeprived adult mouse SGNs.…”
Section: Discussionmentioning
confidence: 99%
“…The somewhat rough isolation procedure may contribute to the discrepancy in the yield of cells from embryonic or neonatal tissue (several thousands) compared with cells from adult inner ear (several hundreds). Previous studies (Zheng and Gao, 1996;Hegarty et al, 1997;Altschuler et al, 1999;Rubel and Fritzsch, 2002;Whitlon, 2004) have demonstrated that NT-3, BDNF, FGF-2, and GDNF can promote SGN survival during development or following deafness caused by ototoxic compounds and noise and trauma. We have extended these findings and demonstrated that coadministration of FGF-2 and GDNF can promote long-term survival of targetdeprived adult mouse SGNs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of cultured SG neurons by Green and coworkers have shown that SG survival is supported both by membrane depolarization and by neurotrophins Hegarty et al, 1997;Zha et al, 2001) and that there are multiple mechanisms underlying the protective effect of depolarization in vitro. Specifically, the survival-promoting effect of depolarization is mediated by L-type voltage gated Ca 2+ channels and involves multiple distinct signaling pathways, including an autocrine neurotrophin mechanism, cAMP production and Ca 2+ /calmodulin-dependent protein kinase (CaMk)-mediated phosphorylation of the transcription factor CREB.…”
Section: Intracochlear Infusion Of Neurotrophinsmentioning
confidence: 99%
“…Multiple factors that increase SGN survival have been identified, including peptide neurotrophic factors such as neurotrophin-3 (NT-3) and brain derived neurotrophic factors (BDNF) (Staecker et al, 1996, Fritzsch et al, 1997, Mou et al, 1997, Roehm and Hansen, 2005 electrical activity also provides a strong survival stimulus both in vitro and in vivo. Depolarization, accomplished by raising extracellular K + ([K + ] o ), promotes SGN survival in vitro (Hegarty et al, 1997) while direct electrical stimulation via an implanted electrode may increase SGN survival after hair cell loss (Lousteau, 1987, Hartshorn et al, 1991, Leake et al, 1991, Mitchell et al, 1997, Leake et al, 1999, Shepherd et al, 2005. Survival responses due to membrane electrical activity require Ca 2+ influx through L-type voltage-gated calcium channels (VGCCs) (Hegarty et al, 1997, Mitchell et al, 1997 and subsequent activation of at least three separate calcium dependent protein kinases: cyclic AMP-dependent protein kinase (protein kinase A, PKA), and Ca 2+ /calmodulin-dependent kinases II and IV (CaMKII, CaMKIV) , Bok et al, 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Depolarization, accomplished by raising extracellular K + ([K + ] o ), promotes SGN survival in vitro (Hegarty et al, 1997) while direct electrical stimulation via an implanted electrode may increase SGN survival after hair cell loss (Lousteau, 1987, Hartshorn et al, 1991, Leake et al, 1991, Mitchell et al, 1997, Leake et al, 1999, Shepherd et al, 2005. Survival responses due to membrane electrical activity require Ca 2+ influx through L-type voltage-gated calcium channels (VGCCs) (Hegarty et al, 1997, Mitchell et al, 1997 and subsequent activation of at least three separate calcium dependent protein kinases: cyclic AMP-dependent protein kinase (protein kinase A, PKA), and Ca 2+ /calmodulin-dependent kinases II and IV (CaMKII, CaMKIV) , Bok et al, 2007. However, excessive Ca 2+ influx is toxic and leads to SGN death (Hegarty et al, 1997).…”
Section: Introductionmentioning
confidence: 99%